2020
DOI: 10.1108/jadee-05-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of technical efficiency and output growth decomposition for small-scale rice farmers in Eastern India

Abstract: Purpose The purpose of this paper is to estimate the degree of technical efficiency, determinants of technical inefficiencies and driving forces behind the production growth for a panel data set collected during the 1998/1999 and 2004/2006 Kharif cropping season, from 452 small-scale rice farming households in the Giridih and Purulia districts of Eastern India. Design/methodology/approach The estimations of technical efficiency utilize stochastic frontier production function with a sub-model of inefficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…For example, (Mishra et al, 2015) found a TE score about 57% for Bangladeshi rice farmers using a large sample covered 2000-2010, whereas (B€ ackman et al, 2011) and (Afrin et al, 2017;Azad and Rahman, 2017) found it to be 0.83 and 0.86, respectively. Similar to our findings, in Eastern India, (Wu, 2020) also found that the small-scale rice farms operate at moderate levels of TE, ranging 23-96% and 26-96% for traditional varieties (TVs) and high-yielding varieties (HYVs), respectively. The difference in the TE scores is likely to be attributed to various reasons, including the size of samples used, rice season and area considered and frontier models utilized.…”
Section: Impacts Of Membership On Technical Efficiency and Yieldsupporting
confidence: 90%
“…For example, (Mishra et al, 2015) found a TE score about 57% for Bangladeshi rice farmers using a large sample covered 2000-2010, whereas (B€ ackman et al, 2011) and (Afrin et al, 2017;Azad and Rahman, 2017) found it to be 0.83 and 0.86, respectively. Similar to our findings, in Eastern India, (Wu, 2020) also found that the small-scale rice farms operate at moderate levels of TE, ranging 23-96% and 26-96% for traditional varieties (TVs) and high-yielding varieties (HYVs), respectively. The difference in the TE scores is likely to be attributed to various reasons, including the size of samples used, rice season and area considered and frontier models utilized.…”
Section: Impacts Of Membership On Technical Efficiency and Yieldsupporting
confidence: 90%
“…The Green Revolution brought new farming technologies to India's attention in the late twentieth century, which greatly enhanced agricultural production and reduced famine. After the Green Revolution, in the eastern rice-growing areas of India, the rate of dissemination of modern technologies was quite slow, which eventually resulted in reduced agricultural output in the region [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Wu (2020) showed moderate technical efficiency in farms in eastern India. Dumagan and Ball (2009) used Fisher and Törnqvist to study growth decomposition in the agricultural sector of the USA, and concluded that output growth was mainly due to the growth of TFP in the sector.…”
Section: Productivity Growth Decompositionmentioning
confidence: 95%